Pengaruh Investasi Asing Langsung, Pengendalian Korupsi, Pertumbuhan Penduduk dan Trade Openness Terhadap Pertumbuhan Ekonomi di Negara Negara G20 Kelompok Upper Middle Income - Zahra Ulfa Sarfika; Oktavira, Dea Riska; Syifa Ariana; M. Afdal Samsuddin (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Economic growth in the G20 countries in the upper middle income group has increased or decreased. The aim is to analyze the influence of foreign direct investment, control of corruption, population growth and trade opportunities on economic growth in the G20 countries in the upper middle income group. The analytical method used in this research is multiple linear regression using the E-views computer program and the data used is panel data. The results of this research explain that the variables of Foreign Direct Investment, Corruption Control, Population Growth and Trade Openness obtained an Fcount value of 2.649623 which is greater than the Ftable in this study of 2.086758 (2.649623 > 2.086758). The conclusion is that the variables of Foreign Direct Investment, Corruption Control, Population Growth and Trade Openness simultaneously have a significant effect on Economic Growth in 8 Upper Middle Income Group Countries.